Integrals Involving Product of Srivastava’s Polynomials and Multiindex Bessel Function: Daya Lal Suthar, Sunil Dutt Purohit, Rakesh K Parmar, Lakshmi Narayan Mishra - Team, Support (Thai Journal of Mathematics, 2021)
The present paper deals with four new generalized integral formulae involving product of Srivastava's polynomials and generalized multiindex Bessel function and are represented in terms of the Fox-Wright function. Various particular cases and consequences of our main results involving the Hermite polynomials are also pointed out.